Strategi Peningkatan Performa Pengelola Pelatihan Pada Pusat Pengembangan Sumber Daya Manusia Aparatur - Maliani, Ani (JURNAL APARATUR, 2019)
Improvement of bureaucratic services today is urgently needed, as science and technology advance. PPSDM Apparatus seizes these opportunities through the development of a number of 44 human resources in leadership, managerial and administrative training for the Ministry of Energy and Mineral Resources in 2018.PPSDM Apparatus oversees the quality of the implementation of training, one of which is using a community satisfaction survey tool, in accordance with the guidelines contained in the Ministry of administrative and bureucratic Reform Regulation No. 14 of 2017. The results showed that training was 70% good and 30% less good.The role of the training providers in creating optimal community satisfaction survey results, especially on the parameters of responsibility, fairness, ability, speed and courtesy of service in accordance with the applicable questionnaire. According to respondents, each of the components above needs to increase which varies from 7% - 43%. The training provide trainers as a team in creating the results of the above services is inseparable from the ability of the team and the individuals to meet the requirements as a manager of training and the results of teamwork. The results of the questionnaire indicated members understand the purpose of carrying out the task, but the attention and care among team members need to be improved. This becomes the author's foundation in highlighting the competency prole of the training providers who are frontliners of the PPSDM apparatus in providing training services, which include core competencies (integrity, customer service orientation, communication and cooperation), role competencies (information seeking, relationship building, results orientation , decision making, focus on regularity, innovation and managing change) and technical competence (carrying out coordination, planning, managing administration, managing administrative education and training and creating a improvement reports). By improving existing capabilities through competency development strategies both classical and non-classical, it can change the ability of training providers so that the value of the community satisfaction survey increases and adds value to the organization.ABSTRAKPeningkatan pelayanan birokrasi dewasa ini sangat dibutuhkan, seiring kemajuan ilmu pengetahuan dan teknologi. PPSDM Aparatur menangkap peluang tersebut diantaranya melalui pengembangan sumber daya manusia sejumlah 44 pelatihan bidang kepemimpinan, manajerial dan administratif untuk lingkup Kementerian Energi Dan Sumber Daya Mineral di tahun 2018. PPSDM Aparatur mengawal kualitas penyelenggaraan pelatihan, salah satunya dengan menggunakan perangkat survei kepuasan masyarakat, sesuai dengan pedoman yang tertera pada peraturan Kemenpan RB No 14 tahun 2017. Hasil Survei kepuasan masyarakat tahun 2018 menunjukanpelatihan bernilai baik 70 % dan bernilai kurang baik 30%. Peranan para penyelenggara pelatihan dalam menciptakan hasil survei kepuasan masyarakat yangoptimal terutama pada parameter tanggungjawab, keadilan, kemampuan, kecepatan dan kesopanan pelayanan sesuai dengan kuesioner yang berlaku. Menurut responden masing-masing komponen diatas perlu peningkatan yang bervariasi mulai dari 7% - 43%. Penyelenggara pelatihan sebagai sebuah tim dalam menciptakan hasil pelayanan tersebut diatas tidak terlepas pada kemampuan tim dan individu dalam memenuhi persyaratan sebagai pengelola pelatihan dan hasil kerjasama tim. Hasil kuesioner menunjukan seluruh anggota memahami tujuan pelaksanaan tugas, namun perhatian dan kepedulian diantara anggota tim perlu ditingkatkan Hal ini menjadi landasan penulis dalam menyoroti pro kompetensi para penyelenggara pelatihan yang menjadi frontliner PPSDM aparatur dalam memberikan pelayanan pelatihan, yang meliputikompetensi inti (integritas, orientasi pelayanan kepada pelanggan, komunikasi dan kerjasama), kompetensi peran (pencarian informasi, membangun hubungan, orientasi pada hasil, pengambilan keputusan, fokus pada keteraturan, inovatif dan mengelola perubahan) dan kompetensi teknis (melaksanakan koordinasi, perencanaan, mengelola penyelenggaraan mengelola administratif penyelenggaraan diklat dan menyusun laporan). Peningkatan kemampuan yang ada melalui strategi pengembangan kompetensi baik klasikal maupun non klasikal dapat merubah kemampuan para penyelenggara pelatihan sehingga nilai survei kepuasan masyarakat meningkat dan memberikan nilai tambah kepada organisasi.